2022
DOI: 10.3389/fonc.2022.870431
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating decisions on aggressive cancer care at end-of-life between patients, family members, and physicians – A qualitative interview study

Abstract: BackgroundPatients with advanced cancer do receive increasingly aggressive end-of-life care, despite it does often not prolong survival time but entails decreased quality of life for patients. This qualitative study explores the unfolding of aggressive end-of-life care in clinical practice focusing on the decision-making process and the quality of end-of-life care from family members’ perspective.Materials and methodsWe conducted semi-structured interviews with 16 family members (six of cancer patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Patients, informal carers and healthcare professionals all often shared the perception of treatment decision-making in advanced cancer as a ‘no choice’-situation. 38 41 , 43 51 In many studies, patient and informal carer participants remarked that the only available option was following the treatment plan offered by the physician. 38 , 39 , 46 , 47 , 50 Participants seldom perceived no treatment as equivalent to treatment, and any choice between broadly equivalent options was perceived as limited, as an oncologist in De Snoo-Trimp et al 44 commented (p. 1184): The concept of “no best option” is, in my opinion, somewhat theoretical because, in practice, there is often a best option based on the tumour and the status of patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients, informal carers and healthcare professionals all often shared the perception of treatment decision-making in advanced cancer as a ‘no choice’-situation. 38 41 , 43 51 In many studies, patient and informal carer participants remarked that the only available option was following the treatment plan offered by the physician. 38 , 39 , 46 , 47 , 50 Participants seldom perceived no treatment as equivalent to treatment, and any choice between broadly equivalent options was perceived as limited, as an oncologist in De Snoo-Trimp et al 44 commented (p. 1184): The concept of “no best option” is, in my opinion, somewhat theoretical because, in practice, there is often a best option based on the tumour and the status of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies showed examples of patients’ experiences of being involved at their preferred level, and that decisions could be a process of reaching a mutual agreement between the physician, patient and informal carers. 37 , 48 , 50 , 51 , 53 , 55 , 56 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is at this moment that the healthcare team may commonly adopt a stance of therapeutic obstinacy through dysthanasia, choosing to implement aggressive and futile procedures and interventions aimed at prolonging the patient's life at any cost, even though they are incapable of reversing the course of the dying process. In dysthanasia, this process becomes more prolonged, and the patient is subjected to intense and unnecessary suffering (8)(9) . It is, therefore, a therapeutic approach that subjects the patient to an undignified, difficult, and excessively painful death, reducing their quality of life in the dying process.…”
Section: Introductionmentioning
confidence: 99%